2017
DOI: 10.1590/0100-69912017001003
|View full text |Cite
|
Sign up to set email alerts
|

Lower extremity reconstruction: epidemiology, management and outcomes of patients of the Federal District North Wing Regional Hospital

Abstract: Objective: to evaluate the management of lower limbs complex traumatic injuries by analyzing their characteristics, types, conduct and evolution, with emphasis on surgical treatment. Methods: we conducted a prospective study of patients treated by Plastic Surgery at a regional hospital of the Federal District during a one-year period. We collected data through serial evaluations and telephone contact records. Results: we studied 40 patients, with a mean age of 25.6 years, predominantly male (62.5%). The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
3
14
0
1
Order By: Relevance
“…16 Lower limb wounds reach a variable spectrum, and are generally caused by high-energy trauma, with extensive skin loss and impaired tissue viability, associated with amputations of limbs or fingers, lacerations, crushing and exposures of noble tissues. 17 In the present study it was observed that maximum injuries 34 (39.53%) were avulsion while 29 (33.72%) injuries were wound with tissue loss. Abrasion and laceration were 12 (13.95%) and 11 (12.79%) of injuries respectively.…”
Section: 75% Present Absentsupporting
confidence: 48%
“…16 Lower limb wounds reach a variable spectrum, and are generally caused by high-energy trauma, with extensive skin loss and impaired tissue viability, associated with amputations of limbs or fingers, lacerations, crushing and exposures of noble tissues. 17 In the present study it was observed that maximum injuries 34 (39.53%) were avulsion while 29 (33.72%) injuries were wound with tissue loss. Abrasion and laceration were 12 (13.95%) and 11 (12.79%) of injuries respectively.…”
Section: 75% Present Absentsupporting
confidence: 48%
“…El colgajo de piernas cruzadas ha sido utilizado con éxito en defectos de cobertura en zona pretibial (2) , zona en que debido a la precaria vascularización cutánea es frecuente encontrar fracaso de partes blandas. Esta técnica ha demostrado buenos resultados en el tratamiento de defectos de cobertura asociados a traumatismos graves, como fracturas de pilón tibial de alta energía (3) o tras sufrir accidentes de tráfico (4) , definiéndose por algunos autores como la alternativa preferida a los colgajos libres en el tratamiento de defectos de partes blandas postraumáticos del miembro inferior (5,6) . Algunos autores incluso han usado el colgajo de piernas cruzadas asociado a terapia VAC de presión negativa con resultados satisfactorios (7) .…”
Section: Discussionunclassified
“…The most common reason microsurgical procedures were not performed was lack of available facilities or microsurgeons or absence of microsurgical equipment (15 of 56 publications, n ¼ 190 of 322, 59.0% of patients). 11,15,17,20,21,[33][34][35][36][37][38][39][40][41] The second most common reason cited as an indication to avoid free tissue transfer was the associated risk (12 of 56 publications, 107 of 322, 33.2% of patients). 14,21,32,37,[39][40][41][42][43][44][45][46] The third most common reason why free tissue transfer was not used was anatomic limitation (28 of 51 publications, n ¼ 170 of 322, 52.8% of patients) described in a variety of ways: no recipient vessels, inadequate vasculature, poor vascular supply, severe arterial injury, vascular damage, extensive zone of injury, lack of vasculature, one vessel run-off, or slight variations on the same language.…”
Section: Indications For Not Performing Free Tissue Transfermentioning
confidence: 99%
“…Other flap types were not described according to common nomenclature, and it was impossible to tell if they were fasciocutaneous or musculocutaneous (n ¼ 83). The majority of publications named the axial blood supply to the flaps described, though in 18 studies, 6,15,17,23,24,[27][28][29][33][34][35]37,45,46,50,52,55,60,63 the blood supply was unknown since it was not named, was described as random (used to describe as many as 136 patients) or was not easily inferred. Of those publications that did name an axial blood supply and made the number of patients with a given axial supply clear, the most common were the posterior tibial artery 25,36,38,42,43,48,53,[56][57][58]66 (11 of 37 publications, n ¼ 50 of 182, 27.5%) and peroneal artery 18,21,31,40,41,51,61,65 (8 of 37 publications, n ¼ 49 of 182, 26.9%) (►Fig.…”
Section: Characteristics Of Transferred Tissuementioning
confidence: 99%
See 1 more Smart Citation